2016
DOI: 10.1186/s40168-016-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal species heterogeneity in the nasal microbiome following antibiotic prophylaxis revealed by tuf gene deep sequencing

Abstract: BackgroundStaphylococci are a major constituent of the nasal microbiome and a frequent cause of hospital-acquired infection. Antibiotic surgical prophylaxis is administered prior to surgery to reduce a patient’s risk of postoperative infection. The impact of surgical prophylaxis on the nasal staphylococcal microbiome is largely unknown. Here, we report the species present in the nasal staphylococcal microbiome and the impact of surgical prophylaxis revealed by a novel culture independent technique. Daily nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
(28 reference statements)
2
15
0
Order By: Relevance
“…The control condition is not required or utilized for MRSA determination but was included to demonstrate the effectiveness of selection. A positive result was anticipated in most control wells due to the high nasal colonization rates of staphylococcal species and the cross-reactivity previously described with the phage cocktail [ 47 , 48 ]. In agreement with expectations, 36 of 40 (90%) samples were positive in the control well.…”
Section: Resultsmentioning
confidence: 99%
“…The control condition is not required or utilized for MRSA determination but was included to demonstrate the effectiveness of selection. A positive result was anticipated in most control wells due to the high nasal colonization rates of staphylococcal species and the cross-reactivity previously described with the phage cocktail [ 47 , 48 ]. In agreement with expectations, 36 of 40 (90%) samples were positive in the control well.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence processing and the definition of ASVs were performed as describe above. Representative ASV sequences were aligned to a Staphylococcus tuf gene database, which includes 36 sequences and 1 sub-species used in McMurray et al [55], and with a sequence from the closest genus to Staphylococcus [56] i.e., Macrococcus canis (accession number: KM45013) as an outgroup (See Supplementary Methods and Supplementary Table 10). Negative extraction controls were included and treated in the same manner as for the 16S rRNA gene sequencing.…”
Section: High-throughput Sequencing Of the Staphylococcus Tuf Genementioning
confidence: 99%
“…However, the 16S rRNA gene has little discriminatory power within the Staphylococcus genus [21,22]. To circumvent this, it is necessary to use other phylogenetic marker genes that have a sufficient level of discriminatory power, such as the gap, hsp60, or tuf genes, when studying complex communities of staphylococcal species [22,23]. Previously, a method has been developed for species-level analysis of staphylococci in the nasal microbiome based on partial sequences of the rpoB gene [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a method has been developed for species-level analysis of staphylococci in the nasal microbiome based on partial sequences of the rpoB gene [24]. Similarly, a previous study applying primers targeting the tuf gene and using only clinical isolates has shown that partial tuf gene amplicon sequencing can be used to unravel staphylococcal communities in the nasal microbiome [23]. Furthermore, the tuf gene has also been used successfully for the identification of CNS species present on the teat apices of dairy cows, albeit using PCR-DGGE [25].…”
Section: Introductionmentioning
confidence: 99%